Hermenêutica bíblica e exemplaridade no Orto do esposo - Pimentel, Antonio Marcos Gonçalves (2007)
About 1385, in the portuguese monastery of Alcobaça, the manuscript of anonymous authorship entitled Orto do Esposo was produced. Built in the literary molds of the exemplariness legitimated by the medieval figure of the auctoritas, the work has as its fulcrum the biblical hermeneutics of the four senses the historical-literal sense; the allegorical sense; the tropological sense; and the eschatological sense its operation and demonstration, becoming separated in four parts or books, each one contends an own theme through which is worked the hermeneutics: of Jesus' name; of the comparison of the Holy Scriptures with the Earthy Paradise; in the correct way to study the Bible; and of the mystic ascetic in that the life of the christians to the time should be ruled. This dissertation intends to investigate the production conditions under which the monastic manuscript from Alcobaça was composed, considering their internal and external aspects, building like this a great social-political-culturalreligious table that frames the text and the scope of the Orto do Esposo. Also the main characteristics of the biblical hermeneutics will be investigated, of the exemplariness, their sources and functions, and similar reputes as allegory, exegesis, testamentary prefiguration, aspects of the XIIIth century portuguese medieval mentality among others. Besides, they will also be considered the query of a mark of authorship front to its dissolution while subjective work, external influences, bibliographical sources and the motivation for the which was written the Orto do Esposo.